Construção de uma fonte EASI-MS (Easy Ambient Sonic-spray Ionization) para análise direta de superfícies e sua aplicação em amostras de interesse forense - Rogerio Araujo Lordeiro (2011)
In this work, an ionization source at atmospheric pressure for surfaceanalysis, named Easy Ambient Sonic-Spray Ionization (EASI-MS), wasconstructed in our laboratory from low cost materials. This source was thus applied to the analysis of forensic samples with excellent results.Initially, cocaine was detected in synthetic solid mixtures at concentrations as low as 0.1% w/w. This concentration is below the detection limit of the reagents usually employed in the preliminary identification of this drug. This methodology also allowed the unambiguous identification of amphetamine derivatives directly from the surface of seized tablets. The direct analysis of blotters suspected of containing LSD was also conducted. All EASI-MS results were confirmed by HPLC-UV measurements. The analysis of paint pen allowed the identification of different components in inks of different colors and different brands, which demonstrated the superior potential of EASI-MS in detecting document fraud. Finally, the detection of the insecticides carbofuran and aldicarb directly from the surface of granules, in a quick procedure that does not involve any pretreatment step, accredits the EASI-MS technique for the detection of these substances, which are linked to frequent occurrences of intoxication and poisoning of humans and animals